2020
DOI: 10.1093/cercor/bhaa138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Sensitivity of Resting-State BOLD Variability to Age and Cognition after Controlling for Motion and Cardiovascular Influences: A Network-Based Approach

Abstract: Recent functional magnetic resonance imaging (fMRI) studies report that moment-to-moment variability in the BOLD signal is related to differences in age and cognition and, thus, may be sensitive to age-dependent decline. However, head motion and/or cardiovascular health (CVH) may contaminate these relationships. We evaluated relationships between resting-state BOLD variability, age, and cognition, after characterizing and controlling for motion-related and cardiovascular influences, including pulse, blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 63 publications
5
30
0
Order By: Relevance
“…The lack of evidence for an association between age‐related effects on RSFA and brain atrophy after adjusting for cardiovascular health is consistent with previous reports using direct physiological measures of neural activity (MEG and EEG): no age‐related associations between RSFA and neuronal indices were detected (Kumral et al., 2020; Tsvetanov et al., 2015). Furthermore, potential age‐related associations between RSFA and cognitive function are fully explained by cerebrovascular risk factors, such as WMH burden (Millar et al., 2020). Taken together these findings suggest that the age‐related differences in BOLD signal variability at resting state are unlikely to be of neuronal origin beyond the effects of age on various types of vascular signals.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of evidence for an association between age‐related effects on RSFA and brain atrophy after adjusting for cardiovascular health is consistent with previous reports using direct physiological measures of neural activity (MEG and EEG): no age‐related associations between RSFA and neuronal indices were detected (Kumral et al., 2020; Tsvetanov et al., 2015). Furthermore, potential age‐related associations between RSFA and cognitive function are fully explained by cerebrovascular risk factors, such as WMH burden (Millar et al., 2020). Taken together these findings suggest that the age‐related differences in BOLD signal variability at resting state are unlikely to be of neuronal origin beyond the effects of age on various types of vascular signals.…”
Section: Discussionmentioning
confidence: 99%
“…Although useful and interesting in their own right ( Tsvetanov et al. 2015 , 2021 ; Millar et al. 2020 ), externally measured vascular and metabolic risk factors that affect cerebral vasculature and associated responses are insufficient for resolving these issues, especially when cross-sectional comparisons and mediation models are used ( Nyberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one study has reported strong correlations between resting-state and task-driven estimates of BOLD variability (Grady & Garrett, 2018); however, these relationships were demonstrated in relatively small samples of 15 older and 20 younger adults. Furthermore, estimates of BOLD variability show fair test-retest reliability over 3-year intervals, at levels comparable to or greater than estimates of functional connectivity (Millar, Petersen, et al, 2020).…”
Section: Introductionmentioning
confidence: 86%
“…Although widespread patterns of age-related reductions in BOLD variability have been observed spanning multiple functional networks, some regional age-related increases in variability have been reported in the same studies. Importantly, these extreme-group (i.e., college-aged students vs. community-dwelling individuals over 60 years old) difference patterns have been replicated in large, continuous aging samples as well (Millar, Petersen, et al, 2020;Nomi, Bolt, Ezie, Uddin, & Heller, 2017;Hu, Chao, Zhang, Ide, & Li, 2014).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation